Dynamics of Civil Structures, Volume 4 Proceedings of the 28th IMAC, A Conference on Structural Dynamics, 2010 - Proulx, Tom.; SpringerLink (Online service). (aNew York, NY Springer New York Imprint: Springer, 2011)
This the fourth volume of five from the 28th IMAC on Structural Dynamics and Renewable Energy, 2010, brings together 29 chapters on the Dynamics of Civil Structures. It presents early findings from experimental and computational investigations of Civil Structures, including studies such as Characterization of a Strongly Nonlinear Laboratory Benchmark System, A Non-destructive Technique for the Health Monitoring of Tie-rods in Ancient Buildings, Estimating Effective Prestress Force on Grouted Tendon by Impact Responses, Experimental Investigation of Dynamic Load Estimation Using Small-scale Testing, and Prediction of Prestress Force on Grouted Tendon by Experimental Modal Analysis.
Keywords: Electronic books; Engineering; Mechanical engineering; Engineering design; Civil engineering; Structural Mechanics